A grandisina e seu análogo isoxazólico previnem o déficit de memória através de efeitos antioxidantes em animais submetidos a um modelo da doença de Alzheimer - Andrade, Victor Hugo Bitencourt de (2024)
Alzheimer's disease (AD) is associated with the deposition of β-amyloid (βA) protein in brain regions such as the cortex (CTX) and hippocampus (HPC), leading to the activation of neurotoxic, oxidative, and inflammatory pathways. Grandisin (GRA) and its isoxazole derivative (IGA) are neolignans with that shows neuroprotective potential, since structurally related compounds have shown to protect neurons against βA in vitro. Additionally, a triazole bioisoster of grandisin prevented cognitive deficits in animals exposed to Aβ by reducing cytokine levels in HPC and lipid peroxidation in CTX and HPC. However, GRA and AIG neuroprotective effects remain unexplored in vivo. This study evaluated GRA and AIG effects on memory and oxidative profiles in an AD mouse model. Male C57/Bl6 mice (CEUA protocol: 1.272/2023) received intracerebroventricular (i.c.v.) Aβ or vehicle injection. After 24 hours, mice underwent daily oral or intraperitoneal (i.p.) treatments with GRA (1 mg/kg), IGA (1 mg/kg), or vehicle for 7 days. Groups included Control i.c.v. /Vehicle (oral or i.p)., βA i.c.v./Vehicle (oral or i.p.), βA i.c.v./GRA (oral or i.p.), and βA i.c.v./IGA (oral or i.p.). At the end of the treatment, the Object Recognition Test (ORT) was performed. Immediately after ORT animals were euthanized for HPC and CTX collection for lipid peroxidation, myeloperoxidase (MPO), and reduced glutathione (GSH) measurement. GRA (i.p.) but not IGA (i.p.) prevented memory deficits and reduced oxidative markers in HPC. Despite GRA (oral) protected memory and improved oxidative profiles, IGA (oral) demonstrated to be superior in memory improvement. These findings show that GRA and its derivative have in vivo neuroprotective effects against βA oligomer-induced damage and suggest that AIG may act as a pro-drug.